Coping in caregivers of family members with traumatic brain injury and the effects on the caregivers' quality of life : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Clinical Psychology at Massey University, Albany, New Zealand - Klum, Maren Annette (Massey University, 2012)
Traumatic Brain Injury (TBI) not only affects the patient but also the family, which is a vital part of the rehabilitation process. Utilising the stress, appraisal, and coping theory developed by Lazarus and Folkman (1984) this study investigated coping in caregivers of a family member with TBI in New Zealand. Most previous research has focused only on psychological morbidity as an outcome measure. However, multiple areas of a caregiver’s life can be affected and a variety of factors can play a role in how caregivers cope. Quality of Life (QoL) is a multidimensional construct that allows for an assessment in physical, psychological, social, and environmental domains. In addition, changes in coping strategies over time were investigated. The hypothesis that emotion-focused coping was related to higher levels of depression and problem-focused coping to lower levels of depression and anxiety was supported. Against expectations, seeking social support was related to higher levels of anxiety. Further findings showed that depression and anxiety were negatively related to QoL and was lower in all domains than in the general population. Emotion-focused coping was negatively related to psychological and environmental QoL, and problem-focused coping was positively related to environmental QoL. In addition, the coping subscales showed a variety of relationships to psychological distress and individual QoL domains. This underlined the importance of investigating individual coping strategies as well as using the multidimensional construct of QoL as an outcome measure. Finally, emotion-focused coping was used most frequently by caregivers in the early years following injury and problem-focused coping most frequently in the later years. The findings are of both clinical and theoretical importance because they add to the understanding of coping in caregivers, how specific coping strategies are related to psychological distress and QoL, and how they change over time. The discussion considers these findings and how they make an important contribution to caregiving research in this population.
Keywords: Traumatic brain injury; Caregivers; Brain injury rehabilitation; Family caregivers; Coping